Acute arterial infarcts in patients with severe head injuries - Agrawal, Deepak; Garg, Anil (Indian Journal of Neurosurgery, 2012)
To study the incidence, demographic profile, and outcome of patients with severe closed head injuries who develop acute arterial infarcts.Patients with severe head injury (Glasgow coma score (GCS) ≤8) presenting within 8 h of injury in the Department of Neurosurgery over a period of 5 months were enrolled in the study. Patients with penetrating head injury, infarct due to herniation and iatrogenic arterial injuries were excluded from the study. Only arterial infarcts developing within 8 h of injury were included in the study. A computed tomography (CT) head was done on all patients within 8 h of injury and repeated if necessary. Arterial infarct was defined as well-demarcated wedge-shaped hypodensity corresponding to an arterial territory on plain CT of the head. Outcome was assessed using Glasgow outcome score (GOS) at 1 month post-injury or at death (whichever came earlier).Forty-four patients of severe head injury were included in the study during the above period. Of these, four patients (9.1%) had arterial infarcts on the initial CT scan. The male:female ratio was 1:3. The mean age was 54 years (range 3–85 years). Two patients had infarcts in the middle cerebral artery distribution and two in the superior cerebellar artery distribution. Poor outcome (GOS 1–3) was seen in 100% of the patients with arterial infarct compared to 52.5% (n=21) in patients with severe head injury without arterial infarct.A significant percentage of patients with severe head injury have arterial infarcts on admission, which may imply arterial injury. Our study shows that these patients have a poorer prognosis vis-à-vis patient without these findings
Keywords: Arterial dissection; arterial infarct; computerized tomography; epidemiology; head injury; trauma